1979
DOI: 10.1111/j.1365-2141.1979.tb01130.x
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin as a Cytosol Iron Transport Intermediate in Human Reticulocytes

Abstract: The major iron-bearing cytosol components of human reticulocytes identified after incubation with 59 Fe-125I-transferrin have been studied further. Component C previously found to behave consistently as an intermediate in the iron transport pathway to haem is shown to consist entirely of ferritin. After a short pulse of labelled transferrin incubation, chase experiments showed a fall of ferritin label with time and a corresponding increase in haemoglobin-iron incorporation. There was no loss of ferritin to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 26 publications
4
15
0
Order By: Relevance
“…This supports the theory that ferritin is not merely an iron-storage molecule, but it can act as an intermediate in iron transport (Speyer and Fielding, 1979). Currently, little is understood regarding the physiological mechanisms of ferritin-iron mobilization.…”
supporting
confidence: 59%
“…This supports the theory that ferritin is not merely an iron-storage molecule, but it can act as an intermediate in iron transport (Speyer and Fielding, 1979). Currently, little is understood regarding the physiological mechanisms of ferritin-iron mobilization.…”
supporting
confidence: 59%
“…As the roles of the H-subunit and L-subunit differ in the mineralization process, the subunit composition of ferritin will influence the metabolic properties of the assembled ferritin molecules (Harrison & Arosio, 1996;Levi et al, 1994). H-subunit rich ferritins have been shown to accumulate and release iron faster than do L-subunit rich ferritins Chiancone & Stefanini, 1984;Wagstaff et al, 1982;Worwood, 1990) and it is suggested that the H-subunit rich ferritins permit more dynamic in-tracellular traffic of iron (Chiancone & Stefanini, 1984;Speyer & Fielding, 1979). L-subunit rich ferritins apparently contain more iron than those ferritins rich in H-subunits (Bomford et al, 1981;Chiancone & Stefanini, 1984) and there are indications that the L-subunit rich ferritins predominate in cell types that play a role in the storage of iron (Boyd et al, 1985;Chiancone & Stefanini, 1984;Coccia et al, 1992;Powell et al, 1975).…”
Section: Isoferritins Different H-subunit/l-subunit Compositions Of Tmentioning
confidence: 99%
“…Although various studies indicate that H-subunit-rich ferritins are more suitable for protecting against oxidative damage, both H-and L-subunitrich ferritins have been shown to reduce the accumulation of ROS. 28 However, H-subunitrich ferritins accumulate and release iron faster than L-subunit-rich ferritins, 14,15,29,30 and it is suggested that the H-subunit-rich ferritins permit more dynamic intracellular traffic of iron, 15,31 while L-subunit-rich ferritins can accumulate more iron, 15,32 and retain iron more firmly than their H-subunit-rich counterparts. 33 It is thus feasible to accept that the increase in the H-and L-subunits of ferritin in osteoarthritis would be to sequester bioavailable iron and to protect against the unwarranted production of ROS.…”
Section: Discussionmentioning
confidence: 99%